Comprehensive analysis about prognostic and immunological role of WTAP in pan-cancer - Lei, Jiangchu; Fan, Yuzhi; Yan, Chaobiao; Jiamaliding, Yeernaer; Tang, Yang; Zhou, Jiawei; Huang, Mengna; Ju, Guomin; Wu, Jian; Peng, Chuanhui (Frontiers in Genetics, 2022)
Background: Wilms tumor 1-associated protein (WTAP) plays a critical role in ribonucleic acid (RNA) methylation of N6 adenosine(m6A) modification, which is closely related with varieties of biological process. However, the role of WTAP in cancers remains to be determined. This study is designed to demonstrate the prognostic landscape of WTAP in pan-cancer and explore the relationship between WTAP expression and immune inﬁltration. Methods: Here, we investigated the expression level and prognostic role of WTAP in pan-cancer using multiple databases, including PrognoScan, GEPIA, and Kaplan-Meier Plotter. Then, applying the GEPIA and TIMER databases, we illustrated the correlations between WTAP expression and immune infiltration in tumors, especially liver hepatocellular carcinoma (LIHC), and esophageal carcinoma (ESCA). Results: WTAP had significant higher expression levels in tumor tissues of ESCA, LIHC, etc., while lower expression levels in those of bladder urothelial carcinoma (BLCA), breast invasive carcinoma (BRCA), etc. And WTAP demonstrated multifaceted prognostic value of WTAP in cancers. Of our interests, WTAP exerted a harmful effect on LIHC patient for overall survival (OS) and progression free survival (PFS). WTAP expression also significantly associated with the infiltration levels of B cells, CD8+ T cells, CD4+ T cells, macrophages, neutrophils and dendritic cells (DC) in LIHC but not ESCA. Furthermore, combined analysis about WTAP expression level and immune cell specific gene markers implied WTAP correlates with regulatory cells (T reg) infiltration in LIHC and ESCA. Conclusion: The m6A regulator WTAP can serve as a prognostic biomarker for certain tumor types in pan-cancer and potentially result from immune cell infiltration.